State of the Sisters - Faludi, Susan (Social Sciences and Development Review, 2016)
The Revolution in support of women’s rights began in America in the 1960s. But, asks a leading expert and theorist, have those considered being role models in the US lost their way- and are the true fighters for feminine dignity and equality now to be found in the developing world?